2014
DOI: 10.1039/c4nr05108d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and assembly of nanomaterials under magnetic fields

Abstract: Traditionally, magnetic field has long been regarded as an important means for studying the magnetic properties of materials. With the development of synthesis and assembly methods, magnetic field, similar to conventional reaction conditions such as temperature, pressure, and surfactant, has been developed as a new parameter for synthesizing and assembling special structures. To date, magnetic fields have been widely employed for materials synthesis and assembly of one-dimensional (1D), two-dimensional (2D) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(89 citation statements)
references
References 259 publications
(238 reference statements)
0
81
1
Order By: Relevance
“…The change in the TGA curve shows the evaporation of CO, CO 2 , NO, Zn [21]. The reduced metal Zinc (Boiling point 908 C) is easily vaporized by heating at 950 C and the mass does not change after 950 C [14,15]. Unlike the other MOFs such as Iron series and Cobalt series, Zinc evaporated from the carbon matrix at high temperature played a pore-forming role, leaving a unique pore structure.…”
Section: Resultsmentioning
confidence: 97%
“…The change in the TGA curve shows the evaporation of CO, CO 2 , NO, Zn [21]. The reduced metal Zinc (Boiling point 908 C) is easily vaporized by heating at 950 C and the mass does not change after 950 C [14,15]. Unlike the other MOFs such as Iron series and Cobalt series, Zinc evaporated from the carbon matrix at high temperature played a pore-forming role, leaving a unique pore structure.…”
Section: Resultsmentioning
confidence: 97%
“…[20][21][22] Given that CNCs are not colloidally stable in such media, coupled with the fact that organic solvents are discouraged in industrial processing, magnetic alignment may offer a more feasible route to produce controllably aligned CNC materials. [23][24][25] Sugiyama et al were the first to show that the magnetic dipole of individual C-O, C-H, and O-H bonds, and their relative orientations in the cellulose polymer chain, led to a material with anisotropic diamagnetic susceptibility. 26 Furthermore, it was observed that the diamagnetic susceptibility is smaller in the direction parallel to the polymer chain axis compared to the perpendicular direction, characterizing cellulose more specifically as a negative diamagnetic anisotropic material.…”
Section: Introductionmentioning
confidence: 99%
“…), which can be widely applied in biomedical and biotechnological fields such as controlled drug delivery and enzyme immobilization [4][5][6]. Among them, poly(N-isopropylacrylamide) (PNI-PAM) gained much attention because it undergo a phase transition from a hydrophilic, water-swollen state to a hydrophobic, globular state when heated above its volume phase transition temperature (VPTT) at 32°C in water [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%